Evaluation of the Physical and Sensory Characteristics of Cocoa Liquor Associated with Sowing Models - Moreno-Martínez, Edith; Gavanzo-Cárdenas, Óscar Mauricio; Rangel-Silva, Fabian Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The promotion of commercial crops of cocoa has increased the use of sowing models, favoring the genetic organization, standardization of the fermentation process and optimizing the quality, obeying the needs of the market and consumer. Taking this into account, the physical and sensory evaluation of four sowing models was carried out in two municipalities: Arauquita (Arauca) and San Vicente de Chucurí (Santander). The models evaluated were the following: Model 1 (M1), self-compatible: FSV41, FTA2, FEAR5; Model 2 (M2), grain size: FSA12, FSA13, FLE3, FLE2; Model 3 (M3), monilia tolerance: CCN51, FEC2, CAU39; Monoclonal Model 4 (M4): CCN51. The physical and sensorial evaluation was carried out by the tasting panel, where also were analyzed: humidity (%), grain index (IG), fermentation (%), and for the cocoa liquor the description of the sensory characteristics of basic flavors was made: cocoa, acidity, bitterness, astringency; specific: fresh fruit, dried fruit, floral, walnut, sweet and others. The non-parametric Wilcoxon test was performed to determine if there were significant differences between each of the variables of the evaluated models. Additionally, a Principal Components Analysis (PCA) was performed to assess the relationship between the evaluated variables and the characteristics of the models. According to the results, the highest grain index was given to M1. In a sensory meaning, the M1 was characterized by having high values ​​in cocoa flavor, fresh fruit, dried fruit, walnut and sweet. The M4 was highlighted by high intensities of acidity, bitterness and astringency sensation. The physical and sensory quality of the sowing models in the two localities did not present significant differences.